City municipalities in the Republic of Serbia - Pešović Marija (Pravni Zapisi, 2019)
The subject of this paper is city municipalities, one of the forms of local government at the lowest level in cities. The process of urbanization, the expansion of cities and the emergence of new ones, creates the need for internal decentralization. Decentralization comes when there is a need and it is estimated that another, lower level of government will perform more efficiently certain jobs. Due to the large number of inhabitants and the growing territory, the big cities are often organized two-step. Municipalities are the result of decentralization and are part of the territorial organization of cities. Although they are not units of local self-government, they have their own administration and affairs delegated by the city government from its own competencies. The regulation of city municipalities, their jobs and the way of financing, as well as a review of comparative solutions in the region, are the main issues discussed in this paper.